Remote Working During Covid-19 Pandemic Situation: Does It Affect Work Engagement? A Study Conducted Among IT Employees - Priya GEORGE; Sony VIJAYAN (Communications of International Proceedings, 2021)
Many organisations have made arrangements for a remote work culture in the new normal created by the Covid-19 pandemic. Due to this pandemic, there is a sudden and drastic shift from a traditional work environment to a remote working environment. Examining the relationship of employee’s remote working to work engagement during the Covid -19 pandemic situation is the main focus of this study. As a result of these changes, there arises a need for organisations to develop a new work engagement strategy that can help even in a post-pandemic era. The data relating to the study were collected from 162 remote working employees working in the IT sector through a structured questionnaire. The study results indicated that there exists a positive correlation between remote working conditions and work engagement. Working remotely for longer hours makes the employee feel isolated and neglected which can lead to reduced performance. The study provides various solutions that an organisation can implement to sustain, support and boost the work engagement levels of remote working employees during the Covid -19 pandemic situation. The study concludes with a discussion pertaining to the scope for future research.
Keywords: Remote working; Work Engagement; Covid -19 pandemic; IT employees